2007
DOI: 10.1002/iroh.200610893
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Impoundment Biomass and Composition of Phytoplankton in the Yangtze River

Abstract: Damming, and thus alteration of stream flow, promotes higher phytoplankton populations and encourages algal blooms (density >10 6 cells L -1 ) in the Three Gorges Reservoir (TGR). Phytoplankton composition and biomass were studied in the Yangtze River from March 2004 to May 2005. 107 taxa were identified. Diatoms were the dominant group, followed by Chlorophyta and Cyanobacteria. In the Yangtze River, algal abundance varied from 3.13 × 10 3 to 3.83 × 10 6 cells L -1 , and algal biomass was in the range of 0.06… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Our approach adds to this 'tool box' of hydrological change prediction and is appropriate not only for Australia but also many other regions where WRD is still increasing. In Central and South America and northern Asia, the damming of tropical rivers for hydroelectric power, navigation and water diversion is an ongoing concern for the ecological integrity of these rivers (Dudgeon, 2000;Anderson et al, 2006a;Anderson et al, 2006b;Zengi et al, 2007). Our findings will have important implications for future decisions concerning the natural resource management of rivers in the Australian tropics and rivers displaying similar characteristics elsewhere in the world.…”
Section: Introductionmentioning
confidence: 85%
“…Our approach adds to this 'tool box' of hydrological change prediction and is appropriate not only for Australia but also many other regions where WRD is still increasing. In Central and South America and northern Asia, the damming of tropical rivers for hydroelectric power, navigation and water diversion is an ongoing concern for the ecological integrity of these rivers (Dudgeon, 2000;Anderson et al, 2006a;Anderson et al, 2006b;Zengi et al, 2007). Our findings will have important implications for future decisions concerning the natural resource management of rivers in the Australian tropics and rivers displaying similar characteristics elsewhere in the world.…”
Section: Introductionmentioning
confidence: 85%
“…However, this prediction has been dismissed by some due to the steep shorelines that provide little habitat for the snail (Jobin, 2005). Upstream of the dam, occurrence of algal blooms within the TGP reservoir have been attributed to increases in residence time (Zeng et al, 2007b). Secondary impacts also extend to other parasitic fauna upstream of TGP, with the reservoir predicted to encourage the proliferation of a fish tapeworm (Bothriocephalus acheilognathi) (Morley, 2007).…”
Section: A Hierarchy Of Impacts At Tgpmentioning
confidence: 99%
“…Diatom blooms are observed worldwide in both lotic (e.g., rivers) [20,35,41] and lentic ecosystems (e.g., lakes and ponds) [31,47,79]. Many studies have found differences in the dominant diatom species among different types of freshwater ecosystems.…”
Section: Introductionmentioning
confidence: 99%